The delivery of essential newborn care in conflict settings: A systematic review - Kampalath, Vinay; MacLean, Sarah; AlAbdulhadi, Abrar; Congdon, Morgan (Frontiers in Pediatrics, 2022)
Introduction Although progress has been made over the past 30 years to decrease neonatal mortality rate, reductions have been uneven. Globally, the highest neonatal mortality rates are concentrated in countries chronically affected by conflict. Essential newborn care (ENC), which comprises key therapeutic interventions for every newborn, such as thermal care, initiation of breathing, feeding support, and prevention of infection, is an important strategy to decrease neonatal mortality in humanitarian settings. We sought to better understand the barriers to and facilitators of ENC delivery in conflict settings. Methods We performed a systematic search of Ovid/MEDLINE, Embase, CINAHL and Cochrane databases using terms related to conflict, newborns, and health care delivery. We also reviewed grey literature from the Healthy Newborn Network and a number of international non-governmental organization databases. We included original research on conflict-affected populations that primarily focused on ENC delivery. Study characteristics were extracted and descriptively analyzed, and quality assessments were performed. Results A total of 1,533 abstracts were screened and ten publications met criteria for final review. Several barriers emerged from the reviewed studies, and were subdivided by barrier level: patient, staff, facility, and humanitarian setting. Patients faced obstacles related to transportation, cost, and access, and mothers had poor knowledge of newborn danger signs. There were difficulties related to training and retaining staff. Facilities lacked supplies, protocols, and data collection strategies. Conclusions Strategies for improved ENC implementation include maternal and provider education and increasing facility readiness through upgrades in infrastructure, guidelines, and health information systems. Community-based strategies may also play an important role in strengthening ENC.